Pemberdayaan Tulis Baca Al-Quran untuk Anak Asuh Perempuan Marginal di Panti Sosial Bina Remaja Harapan Padang Panjang - Afrinaldi Afrinaldi; Miswar Munir (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2020)
The purpose of this essay will want to see about the social homes member to keep having role to play in spiritual development to all boys and girls have been displaced. Little understanding spiritual minirities which were represented by the son of the daycare centers indirectly has a meseareble effect on the quality of the development of human resources. The problem of the most fundamental level the most striking difference for that currently the population in its rates will be they from the people of religius on understanding of, be specific about the level of knowledege of have read many times before Al-quran prescribed in the book. In order to overcome problems it was to know the team devotion is attemping to perform identification to doing mapping the real problems going on. This target is to come up with those of a solution and a replay to its problems that they natural, so that found a methode of and strategies right moment in of redutcing the incidence of on problem currently they have to deal with. Technically there are two the stage in which it is offred by researcheared, and promised to supply: pre-activities through FGD and acctivities the action of through the training reading and writing skills Al-quran. The firs phase: pre different activities FGD illustrate that it is playing one person various informants. The second phase: activities are to be implemented the action of in the forrm of skills training level playing field wrote never so much as read Al-quran illustrated that it is playing two people the source of information in accordance their skills. This activity has been iniciated designed throgh a strategy of ekspository and cooperative learning.